460. SARCOPENIA AFTER NEOADJUVANT CHEMOTHERAPY IS ASSOCIATED WITH DEVELOPMENT OF MODERATE TO SEVERE POST-OPERATIVE COMPLICATIONS IN ESOPHAGOGASTRIC ADENOCARCINOMA PATIENTS. (24th September 2022) - Convill, James; Chmelo, Jakub; Prasad, Pooja; Brown, Joshua; Petrides, George; Phillips, Alexander
Abstract: Sarcopenia is defined as a loss of skeletal muscle mass and function. Preoperative sarcopenia amongst patients with esophageal cancer has been linked to various postoperative complications and to the degree of severity of these complications. The majority of this evidence comes from populations with squamous cell carcinoma or where neoadjuvant chemoradiotherapy was used. Whether sarcopenia pre- or post-neoadjuvant chemotherapy (NAC) for esophagogastric adenocarcinoma (EGA) is associated with postoperative complications is not fully understood. Patients diagnosed with EGA between January 2017 and December 2020 and undergoing NAC followed by esophagectomy from a single high-volume center had their pre- and post-NAC CT scans assessed for radiological sarcopenia. Skeletal muscle index (SMI) was calculated from muscle area measured on CT scans at the level of third lumbar vertebra. Previously published SMI cut off values for radiologically defined sarcopenia were used (52.4cm 2 for men and 38.5cm 2 for women). Post-operative complications were prospectively evaluated and classified using the Clavien-Dindo (CD) classification system. Patients were grouped as either CD 0-I (no-mild complications) or CD II-V (moderate–severe complications). There were 144 patients included in the analysis. 62 patients had FLOT NAC and 82 patients had ECX NAC. Pre-NAC sarcopenia was not associated with the development of moderate–severe postoperative complications (p = 0.075). However, sarcopenia assessed on restaging scan post-NAC was found to be associated with moderate–severe postoperative complications (p = 0.044). EGA patients with sarcopenia post-NAC are more likely to develop moderate–severe post-operative complications than those without sarcopenia. Strategies to treat sarcopenia and prevent its further development are desperately needed in order to reduce post-operative complications.